Silicon drives distinctly the bacterial community in the rhizosphere of maize and common bean - Teixeira, Gelza Carliane Marques [UNESP]; Prado, Renato de Mello [UNESP]; Gonzalez-Porras, Carlos Vital [UNESP]; Ferreira, Patrícia Messias [UNESP]; Carvalho, Lívia Tálita da Silva [UNESP]; Rocha, Sandra Mara Barbosa; da Silva, Janderson Moura; Souza, Thâmara Kelly dos Santos Apollo; Leite, Marcos Renan Lima; Miranda, Rafael de Souza; Pereira, Arthur Prudêncio de Araújo; de Alcântara Neto, Francisco; et al. (Elsevier, 2025)
Silicon (Si) has been recognized as a beneficial nutrient for plants, though its effect on microbial communities within the rhizosphere remains poorly understood, particularly when comparing plant species. This study assessed the effect of Si on the bacterial community in the rhizosphere of two distinct plant species, i.e., common bean and maize, under field conditions. The experiment compared two doses of Si (0 and 12 kg ha⁻1), applied via fertigation, on the bacterial community in the rhizosphere of both species using a randomized complete block design. Soil samples from the rhizosphere were collected at the pod formation stage (R7) for common bean and the tasseling stage (V) for maize. DNA was extracted, and the V4 region of the 16S rRNA gene was sequenced using the Illumina platform. The application of Si slightly separated the bacterial communities in the rhizosphere of both plant species. While Si did not affect bacterial richness and diversity in the rhizosphere of common bean, the rhizosphere of maize showed higher bacterial richness and diversity without Si. The co-occurrence network complexity showed less variation in the rhizosphere of common bean in response to Si, whereas maize exhibited more significant differences between treatments with and without Si. The rhizosphere of maize treated with Si had a higher number of edges (32,729) and positive interactions (10,749) compared to the treatment without Si. This study demonstrated that the bacterial communities in the rhizosphere of maize and common bean respond differently to Si, with Si having a greater impact on the bacterial community in the rhizosphere of maize than in common bean.
Keywords: Amplicon sequencing; Bacteriome; Microbial ecology